2008
DOI: 10.1007/s10811-008-9394-5
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization is more important than experience—results of the first Nordic–Baltic diatom intercalibration exercise 2007 (stream monitoring)

Abstract: The goal of this study was a harmonization of diatom identification and counting among diatomists from the Scandinavian and Baltic countries to improve the comparison of diatom studies in this geographical area. An analysis of the results of 25 diatomists following the European standard EN 14407 during an intercalibration exercise showed that a high similarity was achieved by harmonization and not because of a long experience with diatoms. Sources of error were wrong calibration scales, overlooking of small ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 10 publications
0
40
0
1
Order By: Relevance
“…However, taxon identification uncertainties often contribute much more to overall inconsistency between datasets than other error sources (Kelly, 1997 ;Prygiel et al, 2002 ;Alverson et al, 2003 ;Van der Molen & Verdonschot, 2004 ;Lavoie et al, 2005 ;Besse-Lototskaya et al, 2006 ;Kahlert et al, 2009 ). Even though all uncertainty sources should be minimized as much as possible, we think that agreement on consistent diatom identification will be the greatest challenge in the dataset harmonization.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, taxon identification uncertainties often contribute much more to overall inconsistency between datasets than other error sources (Kelly, 1997 ;Prygiel et al, 2002 ;Alverson et al, 2003 ;Van der Molen & Verdonschot, 2004 ;Lavoie et al, 2005 ;Besse-Lototskaya et al, 2006 ;Kahlert et al, 2009 ). Even though all uncertainty sources should be minimized as much as possible, we think that agreement on consistent diatom identification will be the greatest challenge in the dataset harmonization.…”
Section: Introductionmentioning
confidence: 95%
“…An identification exercise might only consist of a number of samples to be counted and the comparison of the results of the participating laboratories in a report. Still, when the initial comparison is followed by a workshop and agreements on how to handle difficult taxa are attained, between analyst variation can be reduced (Kahlert et al, 2009 ). Evaluations of NorBAF (Nordic-Baltic Network for Benthic Algae in Freshwater, including Sweden, Finland and the Baltic countries) also showed that the workshop was the most appreciated part of the intercalibration exercise, where results were eagerly discussed and clarifications could be made.…”
Section: Overview and Comparison Of Diatom Count Qa In Europementioning
confidence: 99%
See 3 more Smart Citations